Mechanisms of early ettringite formation in ternary CSA–OPC–anhydrite systems. Issue 4 (5th September 2018) - Wolf, Julian Johannes; Jansen, Daniel; Goetz-Neunhoeffer, Friedlinde; Neubauer, Jürgen
Abstract : Ternary systems on the basis of calcium sulfoaluminate (CSA), ordinary Portland cement (OPC) and anhydrite are known for their rapid setting and hardening properties, which are mainly attributed to the formation of ettringite. Ettringite is the major hydrate phase precipitated in the early stages of hydration in these systems and may be formed by three different main reaction pathways. To investigate the process of these mechanisms, the hydration of four different ternary blends were examined by means of heat flow calorimetry, in situ X-ray diffraction, and thermogravimetric analysis. For the CSA-rich mixes, it was found that hydration in the first 48 h is only subject to the behaviour of ye'elimite and anhydrite dissolution and the resulting formation of ettringite. In the system with the highest OPC proportion, the initial hydration kinetics were found to be more rapid, leading to very high ettringite quantities in the first couple of hours. With the dissolution of the anhydrous OPC phases, more ettringite is formed by the hydration of C3 A and the consumption of AH3 stemming from the hydration of ye'elimite and calcium provided by the dissolution of C3 S. In the OPC-rich mixes, more than 50% of the formed ettringite can be attributed to this coupled reaction pathway.